Cultivation of Green Mustard Greens (Brassica juncea L.) on Marginal Land - Sari, Mey Yuni Mustika; Amien, Elhamida Rezkia; Ridwan, Ridwan; Amin, Muhammad (Jurnal Agricultural Biosystem Engineering, 2023)
The research aims to determine the type of fertilizer and watering intensity that can provide optimal and effective growth and production of green mustard greens. The study was conducted in the Greenhouse of the Department of Agricultural Engineering, Faculty of Agriculture, Universitas Lampung. It utilized a Completely Randomized Design (CRD) arranged in a factorial 2 x 3 with three replications. The first factor was the application of fertilizer types, consisting of urea and ghally organic fertilizer. The second factor was the application of watering intensity, which included three levels (watering once a day, every two days, and every three days). The study used sand as the planting medium. The results showed that, in general, the treatment of watering once a day and the application of urea fertilizer provided optimum results in the growth and development of green mustard greens. Meanwhile, the application of ghally organic fertilizer was more efficient in terms of water consumption for green mustard greens. Keywords:  Fertilizer Type, Green Mustard Greens, Marginal Land, Sand, Watering Intensity